A new species of Brachychalcinus (Characiformes: Characidae) from the rio Xingu basin, Serra do Cachimbo, Brazil - Garcia-Ayala, James R.; Ohara, Willian M.; Pastana, Murilo N. L.; Benine, Ricardo C. (Zootaxa, 2017)
Brachychalcinus reisi, a new species of characid fish, is described from the rio Curuá, tributary of rio Iriri, rio Xingu basin, Serra do Cachimbo, Pará State, Brazil. The new species can be distinguished from its congeners by the presence of a series of longitudinal black wavy stripes on the entire body and by a lower number of longitudinal scale rows between dorsal-fin origin and lateral line (7–8 vs. 8–12). Additionally, the new species differs from B. copei, B. parnaibae, and B. retrospina by the lower number of branched dorsal-fin rays (9 vs.10). This is the first description of a new species of the subfamily since the revisionary study of Stethaprioninae, published almost 30 years ago.